Literatura na educação infantil: práticas pedagógicas e a formação da criança pequena - Vilhena, Renata de Almeida Torres (2014)
Based on Freire´s and Piaget´s concepts, this research examines the use of children literacy in teaching practice among small children. The theoretical framework of this research is based on thinkers who understand man as a historical and social being, a epistemic subject that transforms and it is transformed by its action and reaction in the environment in which operates. Understanding literature as culture and, therefore , as part of the process of children formation , we seek to investigate how early childhood educators use literature in their practices , taking under consideration that school is a privileged social tool in one subject formation . We started from the hypothesis that the use of children literacy by teachers who work with small children has not promoted learning processes that foster full development of human capacities such as creativity, curiosity, reflection, as well as the possibility to the child to see the world with/or under the gaze of other . The choice of an kindergarten public school, research universe , was an indication from Municipal Board of Education of São Paulo. Prominent aspects of it are the physical space devoted to reading; and the fact that literacy be focus of study in their Projeto Especial de Ação (PEA). Qualitative in nature, the procedures adopted were a formulated open question interview with teachers; and teaching practice observation in three classrooms. Statements analysis and observation records consisted in content to the critical reflection of empirical reality. The results of this study highlight the importance of language development, oral and written, to the child - in the first stage of basic education - and explicit the need for care and plan context, space and time in the implementation of pedagogical action that occurs in a certain culture. Finally, we hope to contribute with reflections on educational possibilities of reading practice with the child at an initial interaction with the literate world; as well as pedagogical practices which foster an education for freedom, which demands from the child the exercise your ability to analyze texts and contexts, creativity and openness to new perspectives.